Hubungan Kadar C-Reactive Protein (CRP) dengan Jumlah Limfosit pada Pasien TB Paru di BKPM Purwokerto: Relationship of C-Reactive Protein (CRP) Levels with Lymphocyte TB Patiens at BKPM Purwokerto - Santi Safitri; Tantri Analisawati Sudarsono; Dita Pratiwi Kusuma Wardani; Linda Wijayanti (Jurnal Surya Medika (JSM), 2022)
Tuberculosis is a chronic infectious disease that attacks the lung parenchyma. Pulmonary TB is a chronic disease caused by the bacterium Mycobacterium tuberculosis. Pulmonary TB is classified into Pulmonary TB and Extra Pulmonary TB. The prevalence of TB globally is 10 million people; Indonesia ranks second after China and India. This study aims to determine the relationship between levels of C-Reactive Protein (CRP) with the number of lymphocytes in patients with pulmonary TB at BKPM Purwokerto. The research design was in the form of an analytical observational design with an analytical cross-sectional design. The data on the characteristics of the subjects were obtained by filling in the information content, while the levels of C-Reactive Protein (CRP) were used quantitatively and qualitatively, and the number of lymphocytes was measured using a hematology analyzer. There were 30 respondents (60% male and 40% female). There is a relationship with Spearman's correlation test with a value of r = -0.466 and p <0.0001.